Correction to: Predictors of timely diagnostic follow-up after an abnormal Pap test among Hispanic women seeking care in El Paso, Texas - Thelma Carrillo; Jane R. Montealegre; Christina G. Bracamontes; Michael E. Scheurer; Michele Follen; Zuber D. Mulla (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.